A longitudinal investigation of Western Australian families impacted by parental cancer with adolescent and young adult offspring. (4th March 2019) - Morris, Julia N.; Zajac, Ian; Turnbull, Deborah; Preen, David; Patterson, Pandora; Martini, Angelita
Abstract: Objective : Parental cancer is a significant problem for adolescent and young adult offspring. To understand the extent of the problem of parental cancer for Australian offspring, data regarding those impacted are required. The aim of this study was to enumerate and describe the characteristics of Western Australian adolescent and young adult offspring (12–24 years) and their parents with cancer using linked population data. Methods : A retrospective cohort study was conducted using data from the Western Australia Data Linkage System, which provided results generalisable at a national level. Results : Between 1982 and 2015, 57, 708 offspring were impacted by 34, 600 parents' incident malignant cancer diagnoses. The most common diagnosis was breast cancer. Of the 36.4% of parents who died, this was mostly a result of cancer. Most families resided in regional areas and were of high or middle socioeconomic status. Significant predictors of earlier parent death included low socioeconomic status, remoteness, age, having more children and having older children. Conclusion : A considerable number of adolescent and young adult offspring are impacted by parental cancer at a potentially vulnerable age. This research provides knowledge to better understand who is affected by parental cancer in Australia. Implications for public health : These results may be useful for planning and implementation of Australian supportive services.